(untitled) (Archive of Conferences, 2020)
The article is devoted to the content of correctional work in determining the psychological readiness of a child for school. This problem, associated with the successful start of training, determines the most favorable development options that require more or less correctional work of a psychologist. When children enter school, insufficient development of any one component of psychological readiness is often revealed. Many teachers believe that it is easier to develop intellectual mechanisms in the learning process than personal ones. In this regard, the article discusses in detail the options for this point of view on the example of the development of 6-7 year old children.